2015
DOI: 10.1371/journal.pone.0137873
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Quality and Aquatic Invertebrate Metrics Relationships at Patagonian Wetlands Subjected to Livestock Grazing Pressures

Abstract: Livestock grazing can compromise the biotic integrity and health of wetlands, especially in remotes areas like Patagonia, which provide habitat for several endemic terrestrial and aquatic species. Understanding the effects of these land use practices on invertebrate communities can help prevent the deterioration of wetlands and provide insights for restoration. In this contribution, we assessed the responses of 36 metrics based on the structural and functional attributes of invertebrates (130 taxa) at 30 Patag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 40 publications
2
13
1
9
Order By: Relevance
“…Colonizing species (macroinvertebrates) were unaffected by livestock treatments, but richness and density were higher in agricultural ponds than forest ponds. This contrasts with other studies that have shown either a positive (Davis & Bidwell, 2008;Marty, 2005) or a negative (Bouahim et al, 2010;Davidson et al, 2017;Epele & Miserendino, 2015;Foote & Hornung, 2005) effect of grazing on the colonisation of ponds by macroinvertebrates. As these taxa arrived in mesocosms from the surrounding landscape, habitat choice becomes an important factor in their distribution and abundance (e.g.…”
Section: Aquatic Communitycontrasting
confidence: 99%
See 3 more Smart Citations
“…Colonizing species (macroinvertebrates) were unaffected by livestock treatments, but richness and density were higher in agricultural ponds than forest ponds. This contrasts with other studies that have shown either a positive (Davis & Bidwell, 2008;Marty, 2005) or a negative (Bouahim et al, 2010;Davidson et al, 2017;Epele & Miserendino, 2015;Foote & Hornung, 2005) effect of grazing on the colonisation of ponds by macroinvertebrates. As these taxa arrived in mesocosms from the surrounding landscape, habitat choice becomes an important factor in their distribution and abundance (e.g.…”
Section: Aquatic Communitycontrasting
confidence: 99%
“…Similar correlations have been previously observed (e.g. Epele & Miserendino, 2015) and may have resulted from the effects of eutrophication (Gulis, Ferreira, & Graça, 2006;Scheffer, 1990) or macrophyte facilitation and inhibition of invertebrates (De Szalay & Resh, 2000;Kneitel et al, 2017) in aquatic communities.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The use of "reference conditions" has been repeatedly employed as a strategy for managing aquatic communities (Reynoldson et al 1997) and includes documenting the composition of aquatic communities under pristine conditions along gradients of physical and biological conditions (Wright, 1995;Marchant et al 1997;Snodgrass et al 2000). Once we understand how species composition varies with changes in natural gradients, we can predict future changes in biodiversity as the landscape becomes altered by human intervention (Burroni et al 2011, Epele & Miserendino, 2015, 2016 . In this way, we can separate changes in biodiversity due to natural changes in the landscape from humaninduced changes in the landscape (Snodgrass et al 2000).…”
Section: Introductionmentioning
confidence: 99%